Microcystin-RR is a biliary toxin selective for neonatal extrahepatic cholangiocytes - Kapish Gupta; Dongning Chen; Rebecca G. Wells (JHEP Reports)
Background & Aims: Biliary atresia is a fibrosing cholangiopathy affecting neonates that is thought to result from a prenatal environmental insult to the bile duct. Biliatresone, a plant toxin with an α-methylene ketone group, was previously implicated in biliary atresia in Australian livestock, but is found in a limited location and is unlikely to be a significant human toxin. We hypothesized that other unsaturated carbonyl compounds, some with the potential for significant human exposure, might also be biliary toxins. Methods: We focused on the family of microcystins, cyclic peptide toxins from blue-green algae that are found worldwide, particularly during harmful algal blooms. We used primary extrahepatic cholangiocyte spheroids and extrahepatic bile duct explants from both neonatal [a total of 86 postnatal day (P) 2 mouse pups and 18 P2 rat pups (n = 8–10 per condition for both species)] and adult rodents [a total of 31 P15–18 mice (n = 10 or 11 per condition)] to study the biliary toxicity of microcystins and potential mechanisms involved. Results: Results showed that 400 nM microcystin (MC)-RR, but not six other microcystins or the related algal toxin nodularin, caused >80% lumen closure in cell spheroids made from extrahepatic cholangiocytes isolated from 2–3-day-old mice (p <0.0001). By contrast, 400 nM MC-RR resulted in less than an average 5% lumen closure in spheroids derived from neonatal intrahepatic cholangiocytes or cells from adult mice (p = 0.4366). In addition, MC-RR caused occlusion of extrahepatic bile duct explants from 2-day-old mice (p <0.0001), but not 18-day-old mice. MC-RR also caused a 2.3-times increase in reactive oxygen species in neonatal cholangiocytes (p <0.0001), and treatment with N-acetyl cysteine partially prevented microcystin-RR-induced lumen closure (p = 0.0004), suggesting a role for redox homeostasis in its mechanism of action. Conclusions: We identified MC-RR as a selective neonatal extrahepatic cholangiocyte toxin and suggest that it acts by increasing redox stress. Impact and implications:: The plant toxin biliatresone causes a biliary atresia-like disease in livestock and vertebrate animal model systems. We tested the widespread blue-green algal toxin, microcystin-RR, another highly electrophilic unsaturated carbonyl compound that is released during harmful algal blooms, and found that it was also a biliary toxin with specificity for neonatal extrahepatic cholangiocytes. This work should drive further animal studies and, ultimately, studies to determine whether human exposure to microcystin-RR causes biliary atresia.